Publisher Correction: Fish telocytes and their relation to rodlet cells in ruby-red-fin shark (rainbow shark) Epalzeorhynchos frenatum (Teleostei: Cyprinidae) - Hanan H. Abd-Elhafeez (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.